Enhancing Marketing Cooperative for Disabilities Through Digitalization of Accounting Information Systems: Akselerasi Koperasi Pemasaran Difabel Melalui Digitalisasi Sistem Informasi Akuntansi - Rusdianto, Rusdianto; Setiady, Tedy; Ainy, Rintan Nuzul; Sudarmini, Sudarmini; Hidayatullah, Amir; Solichul, Solichul; Iklasenina, Iklasenina; Sirait, Revina; Perdana, Anang Bima; Arifin, Agustian (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
his community service was conducted at the marketing cooperativeof Bangun Akses Kemandirian(Bank) Difabel. The Bank Difabel Cooperativeis a marketing cooperative established on June 21, 2015, by an association of people with disabilities. The motivation behind the establishment of this cooperative is to provide a platform for people with disabilities who have productive economic enterprises to expand their business access and strengthen their capital. The main activity is savings and loans, but the cooperative still faces several issues. Firstly, the savings and loan bookkeeping system and financial reports are still done manually. Secondly, there is a limitation of human resources in managing and developing the cooperative. To address this issue, the PKM team provided assistance and system development. Activities carried out include reviewing the manual financial management, recommending reporting formats, developing a cooperative information system, and training on the use of the cooperative information system. The results of the community service show that the cooperative's management feels supported by the development of the information system, which facilitates the process of recording and reporting finances.